PENGARUH BANK HOSPITALITY, PHYSICAL ENVIRONMENT’S TERHADAP WORD OF MOUTH MELALUI CUSTOMER SATISFACTION PADA PT BANK NEGARA INDONESIA WILAYAH JAKARTA - Hielvita Ludiya; Mufti Nugroho (LPPM Universitas Asa Indonesia, 2019)
The aim of this study is to find out the influence of hospitality and physical environment to gain word by mouth in BNI Bank Jakarta Regional Ofiices mediated by Customer Satisfaction. The sample was selected by purposive technique, totally 104 respondents. The analysis method was multiple regression using SPSS tool. The results showed that bank hospitality, and physical environment have positively influenced customer satisfaction. At the same time, bank hospitality and physical environment have positively influenced word of mouth directly, but negatively by indirectly mediated by customer satisfaction.